Working from Home During and After COVID-19: A Narrative Review of Its Multifaceted Impacts - Sfetcu, Lucian (Technium Social Sciences Journal, 2024)
The COVID-19 pandemic accelerated the global adoption of working from home (WFH), fundamentally altering organizational practices and employee experiences. This narrative review synthesizes current research on the multifaceted impacts of WFH during and after the pandemic, focusing on job satisfaction, productivity, work-family balance, collaboration, innovation, and motivation. A comprehensive literature search was conducted across multiple academic databases, encompassing studies from January 2020 to July 2024 and covering diverse industries and employee demographics. Findings indicate that WFH offers numerous benefits, including increased flexibility, autonomy, and potential productivity gains. However, challenges persist, such as reduced social interaction, blurred work-life boundaries, and potential declines in collaboration and innovation. The effectiveness of WFH is influenced by factors like individual circumstances, job characteristics, technological infrastructure, and organizational support. Hybrid work models are emerging as potential solutions, balancing the advantages of remote work with the need for in-person collaboration. This review highlights the complexities of WFH and underscores the necessity for organizations to develop flexible, inclusive policies that address both employee preferences and operational needs. Further research is recommended to explore long-term impacts and best practices for integrating WFH into sustainable organizational strategies.